2019
DOI: 10.1213/ane.0000000000003517
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity and Sex and Opioid Administration in the Emergency Room

Abstract: Based on National Hospital Ambulatory Medical Care Survey data from 2010 to 2014, an interaction between race/ethnicity and sex exists for administration of opioid analgesia to people of all races/ethnicities presenting to the ED with appendicitis or gallbladder disease, but is much more pronounced for non-Caucasians. These results suggest that disparities in initial opioid management may be predicated on the joint effect of patient race/ethnicity and sex, a condition that may be especially significant for non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…19 Additionally, no statistically significant interactions were discovered between race or ethnicity and opioid administration for individuals presenting to the ED with definitive pain confirmed to originate from the appendix or gallbladder. 20 Moreover, two studies confirmed the frequency of opioids prescribed at discharge was similar between racial and ethnic groups for patients presenting to the ED for long bone fracture. 19,21 In contrast, racial and ethnic disparities were established for non-definitive and more subjectively painful conditions such as back and abdominal pain where a distinct source of pain was not always clearly identifiable.…”
Section: Data Synthesis Summarymentioning
confidence: 84%
See 3 more Smart Citations
“…19 Additionally, no statistically significant interactions were discovered between race or ethnicity and opioid administration for individuals presenting to the ED with definitive pain confirmed to originate from the appendix or gallbladder. 20 Moreover, two studies confirmed the frequency of opioids prescribed at discharge was similar between racial and ethnic groups for patients presenting to the ED for long bone fracture. 19,21 In contrast, racial and ethnic disparities were established for non-definitive and more subjectively painful conditions such as back and abdominal pain where a distinct source of pain was not always clearly identifiable.…”
Section: Data Synthesis Summarymentioning
confidence: 84%
“…A total of six articles remained from which data was extracted and summarized into findings. [17][18][19][20][21][22]…”
Section: Search Results and Study Inclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,7 Studies have examined patient factors associated with receipt of opioids for chronic pain in outpatient settings and postsurgical opioid use; however, to our knowledge, none have examined the patient characteristics associated with the expectation of provision of opioids for acute pain control in outpatient settings. [8][9][10][11] Several studies on postsurgical acute and chronic pain showed that increased anxiety and depression are associated with increased opioid requirement and patients who were anxious had significantly higher pain scores compared with less anxious patients. [12][13][14][15][16][17] Pain catastrophizing, a cascade of negative thoughts and emotions in response to actual or anticipated pain, 18 is shown to predict delayed opioid cessation after surgery 19 as well as predict acute postoperative pain and chronic postsurgical pain.…”
Section: Introductionmentioning
confidence: 99%